A alfabetização de crianças no espectro autista: desafios e possibilidades à luz da literatura - Santos, Natália Amaro dos (Universidade Federal de São Carlos, 2025)
This research aims to identify and analyze scientific publications on the literacy of students with autism spectrum disorder in journals in the field of Special Education, in order to understand the possibilities and challenges involved in this process. To this end, a bibliographic survey was conducted in 6 Special Education journals published between 2002 and 2025. The analysis of the results showed that most of the studies found focus on alphabetic systems; that is, the methodological focus on the code predominates in the literacy of students with autism spectrum disorder. It is considered that there is still a long way to go regarding the production of scientific knowledge on the literacy of students with autism spectrum disorder and methodologies that are inclusive, critical, and effective. This requires putting into perspective the pedagogical conception that underpins the teaching and learning process in the school context, as well as the concrete working conditions of the literacy teacher.
Literacy for children on the autism spectrum: challenges and possibilities in light of literature
Keywords: Alfabetização; Transtorno do Espectro Autista; Práticas Pedagógicas; Educação Especial; Literacy; Autism Spectrum Disorder; Pedagogical Practices; Special Education; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade; 10. Redução das Desigualdades